2021
DOI: 10.3390/lubricants9040037
|View full text |Cite
|
Sign up to set email alerts
|

UV-Visible Spectrophotometer for Distinguishing Oxidation Time of Engine Oil

Abstract: Samples of gasoline engine oil (SAE 5W20) that had been exposed to various oxidation times were inspected with a UV-Visible (UV-Vis) spectrophotometer to select the best wavelengths and wavelength ranges for distinguishing oxidation times. Engine oil samples were subjected to different thermal oxidation periods of 0, 24, 48, 72, 96, 120, and 144 hours, resulting in a range of total base number (TBN) levels. Each wavelength (190.5–849.5 nm) and selected wavelength ranges were evaluated to determine the waveleng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Additional to the displacement of the maximum position, a random variation of the widths of the LSPR bands can be observed in the normalized spectra that could be related with the different oxidation rates of the oil samples. Holland et al [28] found similar results when they studied the oxidation of engine oil at different oxidation times by means of UV-Vis spectroscopy. They focused on an absorbance band of the engine oil and their results show that not all the widths of the absorbance bands become wider as oxidation increases.…”
Section: Uv-vis Spectroscopymentioning
confidence: 66%
“…Additional to the displacement of the maximum position, a random variation of the widths of the LSPR bands can be observed in the normalized spectra that could be related with the different oxidation rates of the oil samples. Holland et al [28] found similar results when they studied the oxidation of engine oil at different oxidation times by means of UV-Vis spectroscopy. They focused on an absorbance band of the engine oil and their results show that not all the widths of the absorbance bands become wider as oxidation increases.…”
Section: Uv-vis Spectroscopymentioning
confidence: 66%
“…The UV-Vis spectrum of the samples, displayed in Figure 4 b, showed a bathochromic shift in the shoulder, indicating the transformation upon ageing. While the sample O A contained only one peak at 346 nm, due to the n- * transitions of the C=O bonds in the oil [ 30 ], the ageing resulted in the emergence of additional peaks at 377 nm, 423 nm, and 453 nm. The peaks were due to the degradation of the long-chain hydrocarbons resulting in the formation of chromophoric moieties [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…The minimum r 2 value requirement varies based on the field and purpose of research. The analytical method validation (AMV) protocols we have employed and read about require a minimum correlation coefficient of 0.990 for HPLC-UV [ 49 ] and 0.950 for a spectrophotometer [ 50 ]. Based on our results, r 2 = 0.997 is quite acceptable.…”
Section: Discussionmentioning
confidence: 99%